Integration of Sportsmanship and Cooperation Values through Physical Education - juhanis, juhanis; Iskandar, Iskandar (SHOOTING: Journal of Sport, Health, and Education, 2025)
This research aims to analyze the integration of sportsmanship and cooperation values through physical education in elementary schools. The study employed a mixed-method approach combining qualitative observations and quantitative assessments of student behavior and attitude changes. Data were collected from 120 elementary students aged 9-12 years across three different schools in Jakarta over a 6-month period. The research utilized pre-test and post-test designs to measure changes in sportsmanship attitudes and cooperative behavior through structured physical education programs. Results indicate that well-designed physical education curricula significantly enhance students' sportsmanship values (p<0.05) and cooperation skills (p<0.01). The integration of traditional games, team sports, and character-building activities proved most effective in developing these values. Students showed improved respect for rules (78% increase), fair play behavior (65% increase), and teamwork skills (82% increase). The study concludes that physical education serves as an effective medium for character development, particularly in fostering sportsmanship and cooperation among elementary students. These findings provide empirical evidence for curriculum developers and educators to prioritize character-integrated physical education programs.